Potent Anticancer, Antioxidant and Antibacterial Activities of Isolated Flavonoids from Asplenium - Jarial, Rini; Thakur, Sveta; Mimi Sakinah, A. M.; Zularisam, A. W.; Sharad, Amit; Kanwar, S. S.; Singh, Lakhveer (Elsevier Ltd, 2018)
Bioactive flavonoids derived from Asplenium nidus (fern) possess potent tumoricidal, anti-bacterial, anti-oxidant activities that are responsible for their chemo-preventive potential against multidrug-resistant (MDR) pathogens, Proteus mirabilis, Proteus vulgaris and Pseudomonas aeruginosa. Fractionation and recognition of the flavonoids were attained through gas chromatography and mass spectrometry (GC/MS). Twelve known and three unknown compounds were revealed by fractions 1 & 3, representing 13.12% and 2.61% out of the total composition (15.12%). Gliricidin7-O-hexoside was found 3.83% followed by quercetin-7-O-rutinoside (3.09%) keampferol-3-O-rutinoside (0.19%) and myricetin-3-O-rhamnoside (1.10%). The anti-bacterial and anti-oxidant activities of present fractions along with pure bioactive constituents were tested against three MDR pathogens through microbroth dilution: MIC50 ranges for amoxicillin, gliricidin7-O-hexoside and quercetin 7-O-rutinoside were 0.0003–0.06 μg/mL, 0.004–0.06 μg/mL and 0.005–6.0 μg/mL, respectively. Gliricidin-7-O-hexoside and quercetin-7-O-rutinoside’s inhibitory activities were comparable to standard antibiotic, amoxicillin (p > 0.05). Herein we report for the first time a number of flavonoids that may act as the source of therapeutically useful compounds against MDR pathogens. In addition, the most extracted flavonoids (gliricidin-7-O-hexoside (78.1%) and quercetin-7-O-rutinoside (69.2%) showed a significant in vitro antioxidant activity i.e. DPPH radical scavenging activity. Both fractions of A. nidus showed obvious cytotoxic effects on human hepatoma HepG2 and human carcinoma HeLa cells. Moreover, the anti-cancer activity generally enhanced with ameliorating antioxidant and antibacterial potential of fern’s flavonoids. These findings illustrate the potential of this fern as a probable source of bioactive constituents and provide a scientific basis for its folklore or ethno-medicinal uses for infectious diseases and cancers.